Value chain analysis of weaving industry - Diah Ayu Rini; Sri Rahayu Budiani (Masyarakat, Kebudayaan dan Politik, 2018)
Value chain analysis is used to discover the distribution of the supply of raw materials and the marketing of industrial products. The research study focus was located in Gamplong Tourism Village, Sleman regency, Daerah Istimewa Yogyakarta. The aims of this research were to 1) map the value chain of the weaving industry in Gamplong Tourism Village; 2) to identify existing obstacles to the weaving industry in Gamplong Tourism Village and 3) to determine appropriate strategies to minimise the obstacles in the weaving industry in Gamplong Tourism Village. The analysis used in this research was a descriptive analysis. The respondents in this study were 47 industry actors, the distributors of raw materials and marketing individuals. Data collection was conducted using a census and in-depth interviews with the weaving industry actors. This was snowballed to the distributor. Based on the results of the research, the value chain of the weaving industrial products as a whole consists of six actors, namely raw material suppliers, raw material distributors, weaving industry actors, distributors, retail traders, and consumers. The household industry value chain diﬀers from the small and medium industry value chain. Some of the obstacles to the Gamplong weaving industry are the length of the value chain, no labour regeneration, and less tourism village development. Therefore, strategies to reduce these obstacles include cutting down the value chains, managing human resources, and increasing the promotion strategies used.